Embodied Violence and Agency in Refugee Regimes : Anthropological Perspectives - Alves de Souza, Mirian; Bauer-Amin, Sabine; Böge, Rozalie E.; Friese, Heidrun; Giritli Nygren, Katarina; Mokre, Monika; Monsutti, Alessandro; Nyhlén, Sara; Schiocchet, Leonardo; Six-Hohenbalken, Maria; Tan, Denise; Yeon Park, Seo (2022)
Multiple refugee regimes govern the lives of forced migrants simultaneously but in an often conflicting way. As a mechanism of inclusion/exclusion, they tend to engender the violence they sought to dissipate. Protection and control channel agency through mechanisms of either tutelage and victimisation or criminalisation. This book contrasts multiple groups of refugees and refugee regimes, revealing the inherent coercive violence of refugee regimes, from displacement and expulsion, to stereotypification and exclusion in host countries, and academic knowledge essentialisation. This violence is international, national, society-based, internalised, and embodied - and it urgently needs due scholarly attention.